2005
DOI: 10.4049/jimmunol.174.12.7618
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Oscillations of Clock Genes, Cytolytic Factors, and Cytokines in Rat NK Cells

Abstract: A growing body of knowledge is revealing the critical role of circadian physiology in the development of specific pathological entities such as cancer. NK cell function participates in the immune response against infection and malignancy. We have reported previously the existence of a physiological circadian rhythm of NK cell cytolytic activity in rats, suggesting the existence of circadian mechanisms subjacent to NK cell function. At the cellular level, circadian rhythms are originated by the sustained transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
142
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(160 citation statements)
references
References 80 publications
13
142
0
5
Order By: Relevance
“…The expression of NK cells oscillates throughout a 24 hour period, with peak expression occurring in the early morning [4]. Numerous other components of the immune system, such as T-helper, T-suppressor and splenic B-cells, also display a 24-hour oscillation similar to that of the NK cells [5].…”
Section: Possible Mechanisms: Clock-controlled Immune Functionmentioning
confidence: 96%
See 1 more Smart Citation
“…The expression of NK cells oscillates throughout a 24 hour period, with peak expression occurring in the early morning [4]. Numerous other components of the immune system, such as T-helper, T-suppressor and splenic B-cells, also display a 24-hour oscillation similar to that of the NK cells [5].…”
Section: Possible Mechanisms: Clock-controlled Immune Functionmentioning
confidence: 96%
“…Despite tremendous efforts to improve our understanding of this cancer, its etiology remains largely unknown with the only well-established risk factor for NHL being immune deregulation [2]. Given that several essential components of the innate immune system are influenced by the 24-hour circadian rhythm [3][4][5], we speculate that circadian disruption might play a role in lymphomagenesis by detrimentally affecting immune activity. Furthermore, we hypothesize that genetic variation in genes responsible for maintaining circadian rhythm might act as a novel panel of biomarkers associated with an individual's susceptibility to NHL.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of such oscillators has been supported by the expression of clock genes in blood cells of both humans (22)(23)(24) and rodents (13,25,26) as well as in lymphoid organs such as bone marrow, thymus, spleen, and lymph nodes (LNs) (13,25,(27)(28)(29)(30)(31). What is the functional consequence of these immune clocks?…”
mentioning
confidence: 99%
“…Chronic inflammation is one of the important pathogenic features of these diseases, which prompted us to hypothesize that circadian clock components may play a role in the regulation of inflammation. Moreover, recent evidence demonstrated that major players in immune function, such as spleen, lymph node, and macrophage and natural killer (NK) cells, contain a cell-autonomous circadian clock (8)(9)(10). Moreover, secretion of cytokines, TNF-α and IL-6 has been reported to display circadian oscillation in macrophages, where ∼8% of transcriptome is under circadian regulation (10).…”
mentioning
confidence: 99%